A Cost-effective Breath-hold Coaching Camera System for Patients Undergoing External Beam Radiotherapy - Akash Mehta; Emma Horgan; Prabhakar Ramachandran; Christopher Noble (Journal of Medical Physics)
Purpose: Organ motion can significantly affect the accurate delivery of radiation doses to the tumor, particularly for sites such as the breast, lung, abdomen, and pelvis. Managing this motion during treatment is crucial. One strategy employed to manage motion induced from respiration is breath-hold (BH), which enhances the geometric precision of dose delivery. Our institute is transitioning to using the ExacTrac Dynamic system to facilitate patient BH using surface-guided cameras. Only 20% of our linacs are equipped with surface guidance capabilities, and due to a high patient stereotactic throughput, the ability to perform in-bunker coaching for BH patients within the bunker is limited. To address this challenge, a time-of-flight camera (ToF) was developed to coach radiotherapy patients undergoing BH procedures, allowing them to gain confidence in the process outside of the bunker and before treatment. Methods: The camera underwent testing for absolute and relative accuracy, responsiveness under various environmental conditions, and comparison with the Elekta Active Breathing Coordinator (ABC) to establish correlation and testing on volunteers independently to assess usability. Results: The results showed that the absolute distance measured by the camera was nonlinear due to square light modulation, which was retrospectively corrected. Relative accuracy was tested with a QUASAR motion phantom, with results agreeing to within ± 2 mm. The camera response was found to be unaffected by changes in lighting or temperature, though it overresponded under extreme temperatures. The comparison with the Elekta ABC system yielded comparable results between lung volume and changes in surface distance during BH. All volunteers successfully followed instructions and maintained BH within ± 1 mm tolerance. Conclusions: This study demonstrates the feasibility of using a cost-effective ToF camera to coach patients before imaging/treatment, saving valuable LINAC linac and imaging system time.